Waterborne epoxy zinc-rich composite coating material and preparation method of composite coating
By modifying carbon fibers with polydopamine, it improves its performance in aqueous epoxy zinc-rich composite coating, and solves the problems of short cathode protection life and poor dispersion of carbon fibers in high corrosion environments, and realizes the coating Improves corrosion resistance and adhesion.
Patent Information
- Application Number
- CN202411744482.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-02-18
AI Technical Summary
The existing epoxy zinc-rich coating has a short cathode protection life in high corrosion environments, mainly affected by the blocking of zinc powder content and self-corrosion on the electrical connection network. The dispersion and compatibility of carbon fibers in epoxy are poor. , affects the mechanical properties and anti-permeability of the coating.
By modifying carbon fibers with polydopamine, it improves its dispersion and compatibility in the aqueous epoxy zinc-rich composite coating, enhances the electrical connection between zinc powder, and improves the bond between carbon fibers and aqueous epoxy resins. , thereby improving the coating's anti-permeability and adhesion.
The modified aqueous epoxy zinc-rich composite coating significantly improves its corrosion resistance and cathode protection in high corrosion environments, and enhances the mechanical properties and adhesion of the coating.
Smart Images

Figure CN119463639A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion coatings, and specifically relates to a water-based epoxy zinc-rich composite coating material and a method for preparing the composite coating. Background Art
[0002] Coating protection is one of the most widely used methods in the field of metal corrosion protection. Most organic coatings mainly exert their protective properties by shielding corrosive particles. Epoxy zinc-rich coatings can not only play a passive protective role through shielding, but also play an active cathodic protection role through anodic oxidation of zinc powder. Therefore, it is widely used in highly corrosive environments such as marine ships and oil fields. However, the cathodic protection life of coatings is often affected by multiple factors, such as zinc powder content, blocking of the electrical connection network by zinc powder self-corrosion, etc. Among them, the effective connection of zinc powder and the improvement of zinc powder utilization are the key to improving this problem.
[0003] As a common plastic modified filler, carbon fiber is often used to improve the mechanical properties of plastics. However, its excellent electrical conductivity is often overlooked. Adding carbon fiber as a filler to epoxy zinc-rich coating can not only increase the electrical connection performance of the coating, but also improve the mechanical properties of epoxy coatings. However, carbon fiber is chemically inert and has almost no active groups on its surface, so its dispersibility and compatibility in epoxy are poor. Summary of the invention
[0004] In view of this, the present invention provides a water-based epoxy zinc-rich composite coating material and a method for preparing the composite coating, and the carbon fiber is modified to improve the mechanical properties and anti-penetration properties of the water-based epoxy zinc-rich composite coating, thereby improving the corrosion resistance of the epoxy zinc-rich coating.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: On the one hand, the present invention provides a water-based epoxy zinc-rich composite coating material, comprising: modified carbon fiber, water-based epoxy resin, zinc powder, an anti-settling agent, a defoaming agent, a water-based epoxy curing agent and a water-based epoxy diluent, wherein the carbon fiber is obtained by modifying polydopamine.
[0006] Preferably, the weight portion of the modified carbon fiber is 0.3-1 part; the weight portion of the water-based epoxy resin is 20-30 parts; the weight portion of the zinc powder is 70-80 parts; the weight portion of the anti-settling agent is 1-3 parts; the weight portion of the defoaming agent is 0.3-0.8 parts; and the weight portion of the water-based epoxy diluent is 0.5-1 part.
[0007] It should be noted that the commonly used anti-settling agents on the market include organic bentonite, silica, etc.; the defoaming agents include fatty alcohol ethoxysiloxane, polyether siloxane, etc.; and the diluents include propylene glycol methyl ether.
[0008] On the other hand, the present invention provides a method for preparing a water-based epoxy zinc-rich composite coating, wherein the material for preparing the water-based epoxy zinc-rich composite coating includes the water-based epoxy zinc-rich composite coating material, and the method for preparing the water-based epoxy zinc-rich composite coating includes the following steps: S1, mixing the modified carbon fiber, water-based epoxy emulsion, defoamer, anti-settling agent and water-based epoxy diluent to obtain a mixed solution A; S2, mixing the water-based epoxy resin curing agent emulsion and the mixed solution A to obtain a mixed solution B; S3, coating the mixed solution B on the surface of the substrate, and drying the mixed solution to obtain a water-based epoxy zinc-rich composite coating.
[0009] Preferably, in step S1, the preparation method of the modified carbon fiber is: first, the carbon fiber, concentrated H2SO4 and HNO3 are mixed and filtered to obtain oxidized carbon fiber; the oxidized carbon fiber is mixed with dopamine hydrochloride to obtain the modified carbon fiber.
[0010] Preferably, the carbon fiber is added to a concentrated H2SO4 and HNO3 mixed solution, oxidized at 50-60°C and 1000-1200 r / min for 20-30 min, filtered, washed and dried to obtain oxidized carbon fiber.
[0011] Preferably, the oxidized carbon fiber and dopamine hydrochloride are mixed, the pH is adjusted to 8.5 using a buffer, and the mixture is centrifuged, washed and dried to obtain modified carbon fiber.
[0012] Preferably, the volume ratio of concentrated H2SO4 and HNO3 is 3:1.
[0013] Preferably, in step S3, the specific steps of drying are: drying at room temperature for 10-14 h, and then curing in a drying oven at 40-50° C. for 24-25 h.
[0014] Preferably, in step S3, the water-based epoxy zinc-rich composite coating has a thickness of 100±10 μm.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention modifies the carbon fiber in the water-based epoxy zinc-rich composite coating by polydopamine. The water-based epoxy zinc-rich composite coating uses the carbon fiber as a modified filler to enhance the electrical connection between zinc powders, and uses polydopamine to modify the surface of the water-based epoxy zinc-rich composite coating to improve its chemical inertness, thereby enhancing the bonding force between the carbon fiber and the water-based epoxy resin, and improving the anti-penetration performance and adhesion of the water-based epoxy zinc-rich composite coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1A curve diagram showing the change of the open circuit potential of the waterborne epoxy zinc-rich composite coating before and after modification versus aging time provided in Example 1 and Comparative Examples 1-3 of the present invention; Figure 2 The impedance model |Z| of the water-based epoxy zinc-rich composite coating before and after modification provided by Example 1 and Comparative Examples 1-3 of the present invention 0.01Hz Curve diagram of changes with aging time; Figure 3 This is a test diagram of the adhesion of the water-based epoxy zinc-rich composite coating before and after modification provided by Example 1 and Comparative Examples 1-3 of the present invention; Figure 4 The present invention provides a flow chart for preparing the water-based epoxy zinc-rich composite coating. DETAILED DESCRIPTION
[0017] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.
[0018] Example 1 Provided is a water-based epoxy zinc-rich composite coating material, wherein the weight portions of the modified carbon fiber, water-based epoxy resin, zinc powder, anti-settling agent, defoaming agent, and water-based epoxy diluent are 0.5 parts, 20 parts, 70 parts, 2 parts, 0.5 parts, and 0.8 parts, respectively.
[0019] A method for preparing a water-based epoxy zinc-rich composite coating is provided, the specific steps of which are: (1) Preparation of modified carbon fiber Carbon fiber (CF) was oxidized: CF was added to a mixed solution of concentrated H2SO4 and HNO3 (3:1, v / v), oxidized at 55 °C and 1100 r / min for 25 min, filtered, washed with ethanol and deionized water respectively, and dried at 60 °C for 24 h for use. The oxidized CF was marked as O-CF.
[0020] The oxidized carbon fibers were modified by adding 0.05 g dopamine hydrochloride into the O-CF suspension (1 mg mL -1 , 100 mL) and ultrasonicated for 1 h. Then 0.61 g of tris(hydroxymethyl)aminomethane was added to the above mixed solution, and the pH was adjusted to 8.5 with HCl (10wt. %) solution, and mechanically stirred at room temperature for 24 h. After centrifugation and deionized water washing, it was dried in an oven at 50°C for 24 h to obtain dopamine-modified CF. The modified CF was labeled as PDA&CF.
[0021] (2) Preparation of waterborne epoxy zinc-rich composite coating PDA & CF were added to the water-based epoxy emulsion and ultrasonically dispersed for 10 min to obtain a uniform emulsion. Defoamer, anti-settling agent and water-based epoxy diluent were added to the mixed slurry in sequence, and zinc powder was added gradually under low-speed stirring. After continuous stirring for 10 min, mixed solution A was obtained.
[0022] Add the water-based epoxy resin curing agent emulsion to the mixed solution A, stir at a low speed, and remove the bubbles in the slurry by ultrasonic and vacuum. Use a film applicator to evenly coat the slurry on the surface of the carbon steel substrate, dry it at room temperature for 12 hours, and then put it in a drying oven at 45 ° C for 24 hours. The coating thickness is 100 ± 10 μm.
[0023] Example 2 Provided is a water-based epoxy zinc-rich composite coating material, wherein the weight portions of the modified carbon fiber, water-based epoxy resin, zinc powder, anti-settling agent, defoaming agent, and water-based epoxy diluent are 0.3 parts, 25 parts, 75 parts, 1 part, 0.3 parts, and 0.5 parts, respectively.
[0024] A method for preparing a water-based epoxy zinc-rich composite coating is provided, the specific steps of which are: (1) Preparation of modified carbon fiber Carbon fiber (CF) was oxidized: CF was added to a mixed solution of concentrated H2SO4 and HNO3 (3:1, v / v), oxidized at 50°C and 1000 r / min for 20 min, filtered, washed with ethanol and deionized water respectively, and dried at 60°C for 24 h for use. The oxidized CF was marked as O-CF.
[0025] The oxidized carbon fibers were modified by adding 0.05 g dopamine hydrochloride into the O-CF suspension (1 mg mL -1 , 100 mL) and ultrasonicated for 1 h. Then 0.61 g of tris(hydroxymethyl)aminomethane was added to the above mixed solution, and the pH was adjusted to 8.5 with HCl (10wt. %) solution, and mechanically stirred at room temperature for 24 h. After centrifugation and deionized water washing, it was dried in an oven at 50 °C for 24 h to obtain dopamine-modified CF. The modified CF was marked as PDA&CF.
[0026] (2) Preparation of waterborne epoxy zinc-rich composite coating PDA & CF were added to the water-based epoxy emulsion and ultrasonically dispersed for 10 min to obtain a uniform emulsion. Defoamer, anti-settling agent and water-based epoxy diluent were added to the mixed slurry in sequence, and zinc powder was added gradually under low-speed stirring. After continuous stirring for 10 min, mixed solution A was obtained.
[0027] Add the water-based epoxy resin curing agent emulsion to the mixed solution A, stir at a low speed, and remove the bubbles in the slurry by ultrasonic and vacuum. Use a film applicator to evenly coat the slurry on the surface of the carbon steel substrate, dry it at room temperature for 10 hours, and then put it in a drying oven at 40 ° C for 24 hours. The coating thickness is 100 ± 10 μm.
[0028] Example 3 Provided is a water-based epoxy zinc-rich composite coating material, wherein the weight portions of the modified carbon fiber, water-based epoxy resin, zinc powder, anti-settling agent, defoaming agent, and water-based epoxy diluent are 1 part, 30 parts, 80 parts, 3 parts, 0.8 parts, and 1 part, respectively.
[0029] A method for preparing a water-based epoxy zinc-rich composite coating is provided, the specific steps of which are: (1) Preparation of modified carbon fiber Carbon fiber (CF) was oxidized: CF was added to a mixed solution of concentrated H2SO4 and HNO3 (3:1, v / v), oxidized at 60 °C and 1200 r / min for 30 min, filtered, washed with ethanol and deionized water respectively, and dried at 60 °C for 24 h for use. The oxidized CF was marked as O-CF.
[0030] The oxidized carbon fibers were modified by adding 0.05 g dopamine hydrochloride into the O-CF suspension (1 mg mL -1 , 100 mL) and ultrasonicated for 1 h. Then 0.61 g of tris(hydroxymethyl)aminomethane was added to the above mixed solution, and the pH was adjusted to 8.5 with HCl (10wt. %) solution, and mechanically stirred at room temperature for 24 h. After centrifugation and deionized water washing, it was dried in an oven at 50 °C for 24 h to obtain dopamine-modified CF. The modified CF was marked as PDA&CF.
[0031] (2) Preparation of waterborne epoxy zinc-rich composite coating PDA & CF were added to the water-based epoxy emulsion and ultrasonically dispersed for 10 min to obtain a uniform emulsion. Defoamer, anti-settling agent and water-based epoxy diluent were added to the mixed slurry in sequence, and zinc powder was added gradually under low-speed stirring. After continuous stirring for 10 min, mixed solution A was obtained.
[0032] Add the water-based epoxy resin curing agent emulsion to the mixed solution A, stir at a low speed, and remove the bubbles in the slurry by ultrasonic and vacuum. Use a film applicator to evenly coat the slurry on the surface of the carbon steel substrate, dry it at room temperature for 14 hours, and then put it in a drying oven at 50 ° C for 25 hours. The coating thickness is 100 ± 10 μm.
[0033] Comparative Example 1 Provided are a water-based epoxy zinc-rich composite coating material and a method for preparing the composite coating. The materials and methods are the same as those in Example 1, except that 0.5 parts of modified carbon fiber in the composite coating material is replaced with 0.5 parts of carbon fiber, and the carbon fiber is directly used to prepare the composite coating.
[0034] Comparative Example 2 Provided are a water-based epoxy zinc-rich composite coating material and a method for preparing the composite coating. The materials and methods are the same as those in Example 1, except that the composite coating is directly prepared without adding modified carbon fiber, and the step of adding modified carbon fiber is removed.
[0035] Comparative Example 3 Provided are a water-based epoxy zinc-rich composite coating material and a method for preparing the composite coating. The materials and methods are the same as those in Example 1, except that the modified natural fiber is replaced with modified carbon nanotubes, and the method steps for modifying the carbon nanotubes are also exactly the same as those in Example 2.
[0036] Performance testing and results (1) Cathodic protection performance Test method: For the waterborne epoxy zinc-rich composite coatings obtained in Example 1 and Comparative Examples 1-3, the cathodic protection performance of the coatings was investigated by an open circuit potential test (OCP).
[0037] Test results: Figure 1 As shown, the open circuit potential of Example 1 and Comparative Examples 1-3 varies with aging time. The open circuit potential results show that the waterborne epoxy zinc-rich composite coating obtained in Example 1 has stronger cathodic protection performance than Comparative Examples 1-3.
[0038] (2) Corrosion resistance Test method: For the waterborne epoxy zinc-rich composite coatings obtained in Example 1 and Comparative Examples 1-3, electrochemical impedance spectroscopy (EIS) was used to examine the corrosion resistance of the coatings.
[0039] Test results: Figure 2 As shown, the low-frequency impedance modulus values |Z| of Example 1 and Comparative Examples 1-3 0.01Hz Curve of change with aging time. |Z| 0.01Hz The results of the change over time show that the water-based epoxy zinc-rich composite coating obtained in Example 1 has higher corrosion resistance and superior durability than those in Comparative Examples 1-3.
[0040] (3) Adhesion test Test method: For the waterborne epoxy zinc-rich composite coatings obtained in Example 1 and Comparative Examples 1-3, the adhesion of the coatings before and after aging was measured using an adhesion tester (PosiTest AT-A).
[0041] Test results: Figure 3 As shown, the adhesion test diagram of the waterborne epoxy zinc-rich composite coating before and after modification of Example 1 and Comparative Examples 1-3 is shown. The adhesion of Example 1 before aging is enhanced compared with Comparative Example 2. After aging, the adhesion of the waterborne epoxy zinc-rich composite coating of Example 1 is much greater than that of Comparative Examples 1-3, indicating that the modified waterborne epoxy zinc-rich composite coating has strong adhesion and durability.
[0042] The specific raw materials not described in the present invention are all existing materials and can be directly purchased from the market.
[0043] The above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A water-based epoxy zinc-rich composite coating material, characterized in that: include: Modified carbon fiber, carbon fiber is obtained by modifying polydopamine; Waterborne epoxy resin; Zinc powder; Anti-settling agent; Defoaming agents; Waterborne epoxy curing agent and, Water-based epoxy thinner.
2. The water-based epoxy zinc-rich composite coating material according to claim 1, characterized in that: The weight proportion of the modified carbon fiber is 0.3-1 parts; the weight proportion of the waterborne epoxy resin is 20-30 parts; the weight proportion of the zinc powder is 70-80 parts; The weight portion of the anti-settling agent is 1-3 parts; the weight portion of the defoaming agent is 0.3-0.8 parts; The water-based epoxy diluent is 0.5-1 part.
3. A method for preparing a water-based epoxy zinc-rich composite coating, characterized in that: The material for preparing the waterborne epoxy zinc-rich composite coating includes the waterborne epoxy zinc-rich composite coating material according to claim 1 or 2, and the preparation method of the waterborne epoxy zinc-rich composite coating includes the following steps: S1, mixing the modified carbon fiber, water-based epoxy emulsion, defoamer, anti-settling agent and water-based epoxy diluent to obtain a mixed solution A; S2, mixing the water-based epoxy resin curing agent emulsion and the mixed solution A to obtain a mixed solution B; S3, coating the mixed solution B on the surface of the substrate, and drying the mixed solution to obtain a water-based epoxy zinc-rich composite coating.
4. The preparation method according to claim 3, characterized in that: In step S1, the preparation method of modified carbon fiber is: first, carbon fiber is added to a mixed solution of concentrated H2SO4 and HNO3, filtered after reaction, to obtain oxidized carbon fiber; and the oxidized carbon fiber is mixed with dopamine hydrochloride to obtain modified carbon fiber.
5. The preparation method according to claim 4, characterized in that: The carbon fiber is added into a mixed solution of concentrated H2SO4 and HNO3, oxidized at 50-60°C and 1000-1200 r / min for 20-30 min, filtered, washed and dried to obtain the oxidized carbon fiber.
6. The preparation method according to claim 4, characterized in that: The oxidized carbon fibers and dopamine hydrochloride are mixed, the pH value is adjusted to 8.5 using a buffer solution, and the modified carbon fibers are obtained after centrifugation, washing and drying.
7. The preparation method according to claim 4, characterized in that: The volume ratio of concentrated H2SO4 and HNO3 is 3:
1.
8. The preparation method according to claim 3, characterized in that: In step S3, the specific steps of drying are: drying at room temperature for 10-14 h, and then curing in a drying oven at 40-50 °C for 24-25 h.
9. The preparation method according to claim 3, characterized in that: In step S3, the thickness of the waterborne epoxy zinc-rich composite coating is 100±10 μm.
Citation Information
Patent Citations
Waterborne epoxy zinc-rich coating with good dispersibility based on graphene
CN113308169A
Primer with gridding conductive characteristic and anodic protection effect as well as preparation method and use method of primer
CN115260875A
Fiber modified anti-corrosion coating for steel pipe pile and preparation method and application of fiber modified anti-corrosion coating
CN117659822A
Modified epoxy resin, bi-component epoxy zinc-rich anticorrosive primer and preparation method of bi-component epoxy zinc-rich anticorrosive primer
CN118667416A
Graphene-type waterborne epoxy zinc-rich coating and preparation method therefor
WO2022267396A1